2021
DOI: 10.7554/elife.67611
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arousal and movement on secondary somatosensory and visual thalamus

Abstract: Neocortical sensory areas have associated primary and secondary thalamic nuclei. While primary nuclei transmit sensory information to cortex, secondary nuclei remain poorly understood. We recorded juxtasomally from secondary somatosensory (POm) and visual (LP) nuclei of awake mice while tracking whisking and pupil size. POm activity correlated with whisking, but not precise whisker kinematics. This coarse movement modulation persisted after facial paralysis and thus was not due to sensory reafference. This phe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 70 publications
5
28
0
Order By: Relevance
“…Strikingly, we found that the whisker trigemino-collicular pathway sends abundant projections to the visual LP in the thalamus, providing an anatomical substrate for the recent findings that the LP integrates visual and tactile information (Petty et al, 2021). The integration of trans-collicular whisker signals in the LP may be an important mechanism underlying visuo-tactile functions such as hunting behavior, in which the SC has been shown to play a key role (Shang et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Strikingly, we found that the whisker trigemino-collicular pathway sends abundant projections to the visual LP in the thalamus, providing an anatomical substrate for the recent findings that the LP integrates visual and tactile information (Petty et al, 2021). The integration of trans-collicular whisker signals in the LP may be an important mechanism underlying visuo-tactile functions such as hunting behavior, in which the SC has been shown to play a key role (Shang et al, 2019).…”
Section: Discussionsupporting
confidence: 60%
“…8). This result provides an anatomical substrate for the recent finding that the LP integrates visual and tactile information [45]. The integration of trans-collicular whisker signals in the LP may be an important mechanism underlying visuo-tactile functions such as hunting behavior, in which the SC has been shown to play a key role [7].…”
Section: Discussionmentioning
confidence: 68%
“…Importantly, similar depolarizations also occurred during pupil dilations in the absence of overt movements of the whisker pad and the running wheel (Fig. S1), suggesting that a significant component of these signals may be associated with changes in arousal rather than movement per se (McGinley et al, 2015a;Petty et al, 2021), with the neural mechanisms of movement adding additional activating and information-containing (e.g. eye position, head direction) signals (Bouvier et al, 2020;Miura and Scanziani, 2021).…”
Section: Discussionmentioning
confidence: 66%
“…metabotropic vs. ionotropic receptors) and understanding these kinetics more fully would narrow the possible underlying mechanisms. Indeed, it is not yet fully known if the mechanisms of cortical activation that are associated with movement results from the activation of movement-related structures, or whether this brain activation represents arousal that is concomitant with movement (McGinley et al, 2015b;Petty et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with a contextual role for LP, recent work found that LP thalamocortical axons projecting to higher visual cortex do not encode a detailed representation of optic flow, which is signaled by corticocortical axons, but rather discrepancies between optic flow and self-motion (Blot et al, 2021). Corticocortical afferents may thus be a principal conduit of feedforward sensory information between cortical areas, whereas higher-order thalamocortical axons may primarily contribute state-dependent contextual modulation of this sensory signaling (Petty et al, 2021; La Terra et al, 2022).…”
Section: Discussionmentioning
confidence: 99%